Manajemen Risiko Proyek dalam Mendukung Keberhasilan Proyek - Muthiara Syahra; Irsyad, Irsyad; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to obtain information on how risk management supports project success. Literature review is the method used in this study. A systematic approach was used to search for and collect data, as well as analyze various literature sources related to project risk management. Data analysis was conducted qualitatively, identifying key patterns from relevant sources. The results indicate that effective and systematic implementation of project risk management plays a crucial role in achieving project success. Effective implementation of risk management in project implementation, including risk identification, analysis, control, mitigation, and monitoring, is a crucial factor in determining project success. Risk management must be integrated into the project life cycle.